Skipjack Tuna (Katsuwonus pelamis) catch in relation to the Thermal and Chlorophyll-a Fronts during May – July in the Makassar Strait. (April 2019) - Hidayat, R; Zainuddin, M; Safruddin, S; Mallawa, A; Farhum, S A
Abstract: Skipjack tuna ( Katsuwonus pelamis ) is a highly migratory fish that has high economic value and wide market acceptance. This research aimed to analyse the relationship between thermal and chlorophyll-a fronts and skipjack tuna catch in coastal waters around Barru, Makassar Strait, Indonesia. This study used two dataset types, data collected in-situ (fishing positions and skipjack tuna catch), and remotely sensed data (Sea-surface temperature and chlorophyll-a, with spatial and temporal resolutions of 4 km and monthly, respectively). Thermal and chlorophyll-a fronts were estimated using a Single Image Edge Detection (SIED) algorithm, and the distances from each catch data point to the nearest fronts was calculated in ArcGIS 10.5. We then analysed the data using the Generalized Additive Model (GAM) statistical model. The results showed that both fronts were detected in every month (May – July). The optimum distance between the thermal front and catch distributions was in the range of 0 - 50 km and the highest catches occurred at a distance of 0 - 10 km with a horizontal gradient of 0.1 - 0.5°C. Meanwhile the distance between the chlorophyll-a front and catch distribution was in the range of 0 - 50 km and the highest catches occurred at a distance of 10 - 20 km with a horizontal gradient of 0.01 - 0.02 mg m −3 . We suggest that skipjack tuna distributions in the study area may be positively associated with the thermal and chlorophyll-a fronts.